Nonsurgical management of type II dens invaginatus with cone beam computed tomography: a rare case - Yilmaz Cirakoglu, Neslihan; Cicek, Ersan (Journal of the Pakistan Medical Association, 2022)
Dens invaginatus is a progressive abnormality resulting from invagination of the crown or root before calcification. This case report presents nonsurgical endodontic treatment and nine-year follow-up results of a right maxillary canine tooth with type II dens invaginatus. A 40-year-old female patient was referred to the clinic for treatment of her maxillary right canine tooth. The invagination was managed on a two-visit appointment. On the first visit, the invagination area, which was disconnected, was completely removed from the root canal. The invagination area was instrumented, and the root canal was dressed with calcium hydroxide. At the second appointment, apexification was done using mineral trioxide aggregate compacted to the apical 3mm. Finally, the invaginated area and the root canal were obturated with a warm vertical compaction technique. At a nine-year follow-up, the invaginated tooth was asymptomatic, and the periradicular lesion showed satisfactory healing radiographically.